Усадьба ожившего мрака - Корсакова Татьяна Владимировна (Королева мистического романа, 2022)
Экземпляры: ф.15 (20240517) / Инвентарный номер: 64702 / Цена: / Сис.шифр: 84(2=411.2)6-4 / Авт.знак: К 69 / ГРНТИ: 17.82.31 / ББК: 84(2=411.2)6-445.1